Implikasi Hukum dari Hubungan Peraturan Menteri dan Peraturan Presiden dalam Sistem Hukum Indonesia - Turiman Turiman; Holijah Holijah; Syahril Jamil (Qistie Jurnal Ilmu Hukum, 2025)
This study examines the legal implications of the relationship between Ministerial Regulations and Presidential Regulations in the Indonesian legal system, focusing on the position and validity of Ministerial Regulations within the hierarchy of legislative regulations. Although Ministerial Regulations are frequently used in government administration, their position is not clearly regulated in Article 7 paragraph (1) of Law No. 12 of 2011 on the Formation of Legislation, which causes confusion in determining their formal position. A functional approach based on Hans Kelsen's theory of Stufenbau des Rechts and the concept of delegated legislation is used to analyze the position of Ministerial Regulations based on the source of their authority, which can originate from laws, government regulations, or presidential regulations. This study finds that the position of Ministerial Regulations should not only be viewed from a formal hierarchy but also from the legal legitimacy derived from their source of authority. The results of this research contribute significantly to regulatory reform by offering a more comprehensive understanding of the position of Ministerial Regulations in a more structured and just Indonesian legal system.